Method for detecting porosity of battery pole piece
By detecting the median particle size and proportion of active materials of the battery pole sheet, combined with the theory of spatial bulk density of spherical particles, the porosity of the battery pole sheet is estimated, and the problems of inaccurate detection and high cost in the prior art are solved, and the problem of inaccurate detection and high cost are achieved. Simple, accurate and economical porosity detection method.
Patent Information
- Application Number
- CN202411699105.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing battery porosity detection methods are inaccurate, cumbersome and costly, which cannot effectively reflect the deep pore conditions, and the equipment precision requirements are high, resulting in large measurement errors.
By detecting the median particle size D50 value of solid powder of coated electrode sheets and rolled electrode sheets, and using the condition that the proportion of solid body of the active material in the electrode sheet slurry is greater than the maximum value of the sphere space stacking density of 74.05%, it is estimated that The porosity of the coated electrode sheet is then derived from the relationship between the coated electrode sheet and the particle size of the material before and after rolling, and the porosity of the rolled electrode sheet is measured using a laser particle size meter.
It realizes porosity detection that is simple and easy to operate, low cost, short time and high accuracy, solves the problems of inaccurate detection results and high cost in the prior art, and provides a popular method.
Smart Images

Figure CN119290709A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a method for detecting the porosity of a battery electrode. Background Art
[0002] Lithium-ion batteries have the characteristics of high voltage, high specific energy, no memory effect, low self-discharge rate and good safety performance. In the production of lithium batteries, the positive / negative current collectors are dried after being coated with slurry, and they also need to be rolled to make the active material particles of the pole piece closely contact to form a good conductive path. Porosity is an important parameter reflecting the degree of rolling of the pole piece. Appropriate porosity can not only obtain good conductivity and better play of active materials, but also play an important role in controlling battery expansion.
[0003] The main methods for calculating porosity are: (1) performing a planar SEM test on the electrode, (2) using a vacuum instrument to measure the vacuum volume and converting it into porosity through calculation; (3) a method for determining the porosity of a lithium-ion battery electrode (patent number: CN112362549 A); (4) a device and method for testing the porosity of a battery electrode (patent number: CN 114720323A); In the above measurement methods: SEM in method (1) can usually only show the morphology of the surface electrode, and cannot truly reflect the porosity of the deep electrode. Since the force from the surface to the collector surface of the electrode during the rolling process is gradually attenuated, the deformation of the surface electrode is the largest. On the other hand, the solvent on the surface dries up first during the coating and baking process, which will cause the solvent to migrate. Therefore, the porosity evaluation using this method is inaccurate; Methods (2) and (3) require too high equipment precision. It takes a long time to measure the accurate real volume of the porous graphite negative electrode; Method (4) uses the Archimedean principle to measure the real volume of the electrode. Since the electrode contains porous silicon and carbon, many bubbles cannot be discharged from the electrode during the process of liquid wetting the electrode, resulting in a large deviation in the calculated real volume.
[0004] Therefore, existing methods for evaluating porosity have problems such as inaccuracy, large measurement errors, and expensive measurement equipment. Summary of the invention
[0005] The main purpose of the present application is to provide a method for detecting the porosity of a battery electrode to solve the problem that the porosity detection method in the prior art is complicated to operate and has high cost.
[0006] In order to achieve the above object, according to one aspect of the present application, a method for detecting the porosity of a battery electrode sheet is provided, and the detection method comprises the following steps:
[0007] Step 1: Obtain the solid powder I of the coating material applied to the electrode, and obtain the median particle size D of the solid powder I50 The value is recorded as D1;
[0008] Step 2: Obtain the solid powder II of the coating material on the rolled pole piece, and obtain the median particle size D of the solid powder II 50 The value is recorded as D2;
[0009] Step 3: The porosity of the rolled pole piece is
[0010]
[0011] Wherein, m+n=1; m is the weight ratio of the active material in the solid powder I to the solid powder I; n is the weight ratio of the total weight of other components in the solid powder I except the active material to the solid powder I.
[0012] Furthermore, the D1 value and / or D2 value is obtained by testing with a laser particle size analyzer.
[0013] Furthermore, the model of the laser particle size analyzer is Mastersizer 3000.
[0014] Furthermore, the process of obtaining a solid powder I of the coating material on the coated electrode includes: dissolving the coated electrode in a solvent I to obtain a solution I, and drying the solution I to obtain a solid powder I.
[0015] Furthermore, the process of obtaining the solid powder II of the coating material on the rolled pole piece includes: dissolving the rolled pole piece in a solvent II to obtain a solution II, and drying the solution II to obtain a solid powder II.
[0016] Furthermore, the weight ratio of the coated electrode and the solvent I is 1:(2-5).
[0017] Furthermore, after the coated electrode is dissolved in solvent I, the filtrate is filtered through a 100-mesh sieve to obtain solution I.
[0018] Furthermore, the weight ratio of the rolled pole piece to the solvent II is 1:(2-5).
[0019] Furthermore, after the rolled electrode is dissolved in solvent II, the filtrate is filtered through a 100-mesh sieve to obtain solution II.
[0020] Furthermore, the temperature of drying I is 150-200° C., and the time of drying I is 30-60 min.
[0021] Furthermore, the temperature of drying II is 150-200° C., and the time of drying II is 30-60 min.
[0022] Furthermore, both drying I and drying II are dried in a suspended air-blast oven.
[0023] Furthermore, the electrode piece is a positive electrode piece or a negative electrode piece of a ternary lithium battery.
[0024] Furthermore, the solvent used to dissolve the positive electrode plate is selected from one or more of N-methylpyrrolidone, dimethylformamide and ethylene glycol.
[0025] Furthermore, the solvent used to dissolve the negative electrode plate is selected from one or more of pure water, acetone, methanol, ethanol and isopropanol.
[0026] Furthermore, the active material is a positive electrode active material or a negative electrode active material.
[0027] Further, other components besides the active material include a conductive agent, a binder and an auxiliary agent.
[0028] Further, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium cobalt oxide.
[0029] Further, the negative electrode active material includes one or more of graphite, silicon carbon and silicon oxygen.
[0030] Further, the conductive agent includes one or more of conductive graphite, conductive carbon black, carbon nanotubes and carbon fibers.
[0031] Further, the binder includes one or more of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na).
[0032] Furthermore, the auxiliary agent includes one or more of lithium carbonate, oxalic acid, vinyl sulfate (VS), dimethyl sulfate (DMS) and diethyl oxalate (DEP).
[0033] The technical solution of the present application provides a method for detecting the porosity of a battery electrode, by detecting the median particle size D of the coating powder in the electrode after coating and the coating powder in the electrode after rolling. 50 The porosity a of the coated electrode is estimated based on the condition that the solid proportion of active materials in the electrode slurry is greater than 74.05% of the maximum spherical space packing density and the weight proportion of the main material and the secondary material in the coating material of the coated electrode. Then, the porosity of the coated electrode and the particle size D of the material before and after rolling are calculated. 50 The porosity calculation method in the rolled pole piece is derived from the relationship between them; the porosity detection method innovatively designed in this application is simple, easy to use, low cost, short time, and the accuracy can meet the use requirements, and can be promoted for use. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The drawings in the specification, which constitute a part of the present application, are used to provide further understanding of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute improper limitations on the present application.
[0035] Figure 1 The particle size distribution diagram of the solid powder material I coated on the pole piece in Example 1 of the present application is shown;
[0036] Figure 2 The particle size distribution diagram of the solid powder II rolled pole piece of Example 1 of the present application is shown;
[0037] Figure 3 The particle size distribution diagram of the solid powder material I coated on the pole piece in Example 2 of the present application is shown;
[0038] Figure 4 The particle size distribution diagram of the solid powder II rolled pole piece of Example 2 of the present application is shown;
[0039] Figure 5 A scanning electron microscope image of the rolled pole piece of Comparative Example 1 of the present application is shown;
[0040] Figure 6 A scanning electron microscope image of the rolled pole piece of Comparative Example 2 of the present application is shown;
[0041] Figure 7 A scanning electron microscope image of the rolled pole piece of comparative example 3 of the present application is shown. DETAILED DESCRIPTION
[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0043] The present application provides a method for detecting the porosity of a battery electrode, which can solve the problems of high cost and inaccurate detection results in traditional electrode porosity evaluation methods.
[0044] The method for detecting the porosity of the electrode sheet of the present application comprises the following steps:
[0045] Step 1: Obtain the solid powder I of the coating material applied to the electrode, and obtain the median particle size D of the solid powder I 50 The value is recorded as D1;
[0046] Step 2: Obtain the solid powder II of the coating material on the rolled pole piece, and obtain the median particle size D of the solid powder II 50 The value is recorded as D2;
[0047] Step 3: The porosity of the rolled pole piece is
[0048]
[0049] Wherein, m+n=1; m is the weight ratio of the active material in the solid powder I to the solid powder I; n is the weight ratio of the total weight of other components in the solid powder I except the active material to the solid powder I.
[0050] In the porosity calculation formula of the rolled pole piece of this application, is the porosity of the coated pole piece, that is, the porosity a of the coated pole piece before rolling is calculated first, and the theoretical estimation method of a includes:
[0051] ① The main components of lithium battery slurry are: positive / negative electrode materials, binders, conductive agents, and auxiliary additives. The solid content of the positive and negative electrode materials is 90-97%, which is greater than the maximum spatial packing density of the sphere, 74.05%. Therefore, the porosity a of the coated electrode can be estimated approximately using the solid ratio in the slurry making process;
[0052] ② The ratio of the main material and other solid materials in the lithium battery slurry, recorded as m and n (where m+n=1);
[0053] ③ The porosity a of the coated electrode can be estimated as:
[0054]
[0055] Porosity of rolled pole piece It can be approximately expressed as;
[0056]
[0057] Among them, the calculation formula The theoretical basis is as follows:
[0058] (1) The main material particles are spherical particles, which can be stacked according to the space utilization of face-centered cubic closest packing: the stacking method is ABAB stacking, assuming that the radius of the sphere is r, a = 2r, and there are 2 in the entire hexagonal unit cell; the volume of the spherical particle is: Vball = 8πr 3 / 3; the volume of the hexagonal unit cell is: Vcrystal = 8ⅹ2 1 / 2 ⅹr 3 ; The space utilization is:
[0059] (2) For lithium batteries, the main material accounts for 90-97% and the remaining solid accounts for 3-7%. The content of the main material is much greater than the content of the remaining solid. Therefore, it can be approximately expressed that the remaining solids are distributed in the gaps after the main material is densely packed. Therefore, "n / m" is the spatial packing density of solids other than the main material converted into particles similar to the main material in equal proportion;
[0060] (3) The formula 74.05% x (1 + n / m) is the spatial occupancy of all solids;
[0061] (4) Formula 1-74.05% x (1 + n / m) is the porosity in all pole pieces.
[0062] (5) Rolling can be understood as: the main material is deformed under pressure, and the spatial structure of the main material particles is manifested as a change in particle size, that is, the particle size before rolling (after coating) is D1, and the particle size after rolling becomes D2;
[0063] (6) The volume calculation formula of a sphere is: V = 4πR 3 / 3, the volume of the sphere and the radius R 3 The radius R is proportional to the diameter D, so the volume of the sphere V∝R 3 ∝D 3 ; The volume change of spherical particles during rolling can represent the change of porosity after rolling, so it is (D2 / D1) 3 Therefore, according to the above formula To calculate the porosity of the rolled battery pole piece.
[0064] The present application provides a method for detecting the porosity of a pole piece, by detecting the D 50 The porosity a of the coated electrode is estimated based on the condition that the solid content of the active material in the electrode slurry is greater than 74.05% of the maximum value of the spherical space packing density and the weight ratio of the main material and the secondary material in the coating material of the coated electrode (a = [1-(1+n / m) x 74.05%]); then, based on the porosity of the coated electrode and the median particle size D of the material particles before and after rolling, the porosity of the coated electrode is estimated based on the porosity of the coated electrode and the median particle size D of the material particles before and after rolling. 50 The porosity calculation method in the rolled pole piece is derived from the relationship between . The porosity detection method innovatively designed in this application is simple and easy to implement, low in cost, short in time, and has an accuracy rate that meets the use requirements, and can be promoted for use.
[0065] In some embodiments, the particle size D1 value of the solid powder I for coating the pole piece and / or the particle size D2 value of the solid powder II for rolling the pole piece are obtained by testing using a laser particle size analyzer; for example, the laser particle size analyzer model used is Mastersizer 3000.
[0066] The present application adopts a laser particle size analyzer to detect the particle size in the powder, and the detection result is accurate, the operation is convenient, and the cost is low; the accuracy of the subsequent calculation results can be guaranteed only when the median particle size measurement is accurate.
[0067] In some embodiments, the process of obtaining a solid powder I of the coating material on the coated electrode includes: dissolving the coated electrode in a solvent I to obtain a solution I, and drying the solution I to obtain a solid powder I.
[0068] In the steps of this application, the slurry is first coated on the current collector to form a coating, and then dried and stabilized to form a coated pole piece. At this time, each component is evenly distributed in the slurry, and then a suitable solvent is used to dissolve the coating slurry, and then the solvent is removed to change the liquid slurry into a solid powder, that is, to obtain the solid powder I of the slurry. At this time, in the accumulation state of the coating material particles of the coated pole piece, since the main material of the slurry is the active material, which accounts for more than 90%, the packing density of the active material particles is greater than the theoretical maximum value of the spherical space packing density of 74.05%. At this time, there are other components such as conductive agents, binders and other additives. The particles will also occupy a certain space, that is, the physical space occupied by all particles in the coating material of the coated pole piece should be greater than the known theoretical calculated value of 74.05%. Then, according to the weight ratio of other materials and main components, it is estimated that the space occupied by other materials should be 74.05% of the space ratio, and the total space is 100%. After calculating the physical space occupied by all particles, the remaining space percentage is the space not filled by particles, that is, the total porosity in the coated pole piece.
[0069] In some embodiments, the process of obtaining a solid powder II of the coating material on the rolled pole piece includes: dissolving the rolled pole piece in a solvent II to obtain a solution II, and drying the solution II to obtain a solid powder II.
[0070] In the steps of the present application, the coated electrode is first rolled to promote a tighter stacking of particles in the coating material. This step is also a routine operation for preparing electrodes. A suitable solvent is then used to dissolve the coating slurry with more tightly packed particles after rolling, and the solvent is removed to change the liquid slurry into a solid powder, i.e., solid powder II of the slurry is obtained. In this process, the slurry composition does not change from the coated electrode state to the rolled electrode state, but the coating material particles of the unrolled coated electrode have a larger particle size and are not tightly packed, while the coating material particles of the rolled electrode have a smaller particle size and are more tightly packed. The particles will be squeezed and rearranged in space according to the rolling conditions. At this time, the porosity of the coating material of the rolled electrode has changed. As the particle size becomes smaller, the pores may be properly filled, and the extent of the porosity decrease can be estimated by the volume amplitude of the particle size reduction.
[0071] In some embodiments, the weight ratio of the coating electrode to the solvent I is 1:(2-5). The present application adopts this ratio to dissolve the coating material as completely as possible without increasing the time and cost of later solvent removal.
[0072] In some embodiments, after the coated electrode is dissolved in solvent I, the filtrate after filtering through a 100-mesh screen is solution I. The present application can obtain a solution with relatively uniform particle size through filtering, which is convenient for obtaining accurate particle size measurement results later.
[0073] In some embodiments, the weight ratio of the rolled pole piece to the solvent II is 1:(2-5). The present application adopts this ratio to dissolve the coating material as completely as possible without increasing the time and cost of later solvent removal.
[0074] In some embodiments, after the rolled pole piece is dissolved in solvent II, the filtrate is filtered through a 100-mesh screen to obtain solution II. The present application can obtain a solution with relatively uniform particle size through filtration, which is convenient for obtaining accurate particle size measurement results later.
[0075] In some embodiments, the temperature of the drying process I is 150-200° C., and the time of the drying process I is 30-60 min.
[0076] In some embodiments, the temperature of drying II is 150-200° C., and the time of drying II is 30-60 min.
[0077] The above drying temperature and time are applicable to both solution I and solution II. The temperature and time of the two can be the same or different and can be adjusted according to actual conditions. The ultimate goal is to obtain solid powder.
[0078] In some embodiments, both drying I and drying II are dried in a suspended air blast oven. The above-mentioned suspended air blast oven used in this application is suitable for drying powder materials, and has a better drying effect.
[0079] In some embodiments, the solvent used to dissolve the positive electrode sheet is selected from one or more of N-methylpyrrolidone, dimethylformamide and ethylene glycol. The above solvent selected in this application is more suitable for positive electrode materials, and the solvent can dissolve the positive electrode coating material in the positive electrode sheet.
[0080] In some embodiments, the solvent used to dissolve the negative electrode plate is selected from one or more of pure water, acetone, methanol, ethanol and isopropanol; for example, ethanol. The above solvents selected in this application are more suitable for negative electrode materials, and the solvent can dissolve the negative electrode coating material in the negative electrode plate.
[0081] In some embodiments, the electrode piece is a positive electrode piece or a negative electrode piece of a ternary lithium battery. The detection method of the present application can be applied to detect the porosity of the positive electrode piece and the negative electrode piece of a ternary lithium battery, and the detection result is accurate.
[0082] In some embodiments, the active material is a positive electrode active material or a negative electrode active material.
[0083] In some embodiments, other components besides the active material include conductive agents, binders, and auxiliary aids.
[0084] In some embodiments, the positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium cobalt oxide. The positive electrode active material in the detection method of the present application is not limited to the above, and can also be other types of active ingredients, and their particle space occupancy has exceeded 74.05%.
[0085] In some embodiments, the negative electrode active material includes one or more of graphite, silicon carbon and silicon oxygen. The negative electrode active material in the detection method of the present application is not limited to natural graphite, but may also be other types of active ingredients, and the particle space occupancy thereof exceeds 74.05%.
[0086] In some embodiments, the conductive agent includes one or more of conductive graphite, conductive carbon black, carbon nanotubes and carbon fibers; the binder includes one or more of polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR) and sodium carboxymethyl cellulose (CMC-Na); the auxiliary agent includes one or more of lithium carbonate, oxalic acid, vinyl sulfate (VS), dimethyl sulfate (DMS) and diethyl oxalate (DEP). Other components of the present application may also include other types, not limited to the above.
[0087] In some embodiments, the single-sided coating density of the coated electrode is 13-14.5 mg / cm 2 ; Double-sided coating surface density is 27-28.5 mg / cm 2 ; The coated current collector includes aluminum foil; the thickness of the aluminum foil is 15 to 17 μm; the thickness of the rolled pole piece is 102 to 104 μm.
[0088] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0089] Example 1
[0090] (1) preparing a ternary lithium battery positive electrode slurry, wherein the solid raw materials are: ternary main material (NCM523), conductive agent (Super-P), lithium carbonate, polyvinylidene fluoride (PVDF), and the solid mass ratio is 93.5:4.0:0.5:2.0. The solvent is N-methylpyrrolidone (NMP). The amount of solvent NMP added is adjusted, and the slurry solid content is prepared by stirring and dispersing to obtain 67%;
[0091] (2) Double-sided coating is performed using an extrusion slit coating device. The coated electrode is dried in a suspended blast oven. The weight loss ratio of the coated electrode after baking is ≤1000ppm, and the single-sided coating surface density is 13.80±0.21mg / cm 2 , double-sided coating surface density is 27.60±0.41g / cm2 , the current collector used for coating is aluminum foil, and the thickness of the aluminum foil is 16±1μm;
[0092] (3) The coated electrode is rolled, and the thickness of the electrode after rolling is 103±1μm (including foil);
[0093] (4) Weigh 50 g (including foil) of the coated electrode, measure 200 g of NMP solution and pour it into a beaker, cut the electrode into small pieces of 3 cm x 3 cm and place them in the beaker, use a glass rod to slowly stir until the slurry on the electrode is completely dissolved, pass the solution through a 100 mesh sieve to obtain a filtrate, and place the filtrate in an oven for baking for 30 to 60 min to obtain a solid powder, and the baking temperature is 180 ° C;
[0094] (5) Take the solid powder in (4) and use a laser particle size analyzer Mastersizer 3000 to measure the particle size distribution. The particle size distribution diagram is as follows: Figure 1 As shown, the test D 50 The value is 11.321 μm;
[0095] The measurement process is as follows: (a) Take a small amount of the sample to be tested and dissolve it in 60 ml of distilled water, and use a glass rod to stir ultrasonically for 60 seconds; (b) Click "Initialize Instrument" in the test software, and start adding samples when the laser percentile of "Measurement Background" jumps to 0.00% after initialization; (c) Use a disposable dropper to slowly drip the sample solution into the beaker to be tested, and stop adding samples when the laser percentile is 5-15%, and start testing;
[0096] (6) Weigh 50 g (including foil) of the rolled electrode, measure 200 g of NMP solution and pour it into a beaker, cut the electrode into small pieces of 3 cm x 3 cm and place them in the beaker, use a glass rod to slowly stir until the electrode slurry is completely dissolved, pass the solution through a 100 mesh sieve to obtain a filtrate, and place the filtrate in an oven for baking for 30 to 60 min to obtain a solid powder, and the baking temperature is 180 ° C;
[0097] (7) Take the solid powder in (6) and use a laser particle size analyzer to measure the particle size distribution. The particle size distribution diagram is as follows: Figure 2 As shown, the test D 50 The value is 11.265μm;
[0098] (8) The proportions of the main positive electrode material and other solid materials are m = 93.5%, n = 6.5%, and the particle size distribution of the powder material for coating the electrode and rolling the electrode is obtained by testing the particle size distribution of the powder material. 50 The values are D1 = 11.321 μm, D2 = 11.265 μm, and the calculation results are:
[0099]
[0100] Example 2
[0101] (1) preparing a negative electrode slurry for a ternary lithium battery, wherein the solid raw materials are: natural graphite, a conductive agent (KS-6), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), and the solid mass ratio is 95.5:1.5:1.3:1.7, and the solvent is deionized water (H2O). The amount of solvent NMP added is adjusted, and the slurry solid content is prepared by stirring and dispersing to obtain 45%;
[0102] (2) Double-sided coating is performed using an extrusion slit coating device. The coated electrode is dried in a suspended blast oven. The weight loss ratio of the coated electrode after baking is ≤3000ppm, and the single-sided coating surface density is 7.07±0.11mg / cm 2 , double-sided coating surface density is 14.14±0.21g / cm 2 , the current collector used for coating is copper foil, and the thickness of copper foil is 10±1μm;
[0103] (3) The coated electrode is rolled twice, the thickness of the first rolling is 110±1μm (including foil), and the thickness of the electrode after the second rolling is 100±1μm (including foil);
[0104] (4) Weigh 60g (including foil) of the coated electrode, measure 200g of alcohol and pour it into a beaker, cut the electrode into small pieces of 3cm x 3cm and place them in the beaker, use a glass rod to slowly stir until the slurry on the electrode is completely dissolved, pass the solution through a 100-mesh sieve to obtain a filtrate, place the filtrate in an oven and bake for 30 to 60 minutes to obtain a solid powder, and the baking temperature is 150°C;
[0105] (5) Take the solid powder in (4) and use a laser particle size analyzer to measure the particle size distribution. The particle size distribution diagram is as follows: Figure 3 As shown, the test D 50 The value is 20.424 μm;
[0106] (6) Weigh 60 g (including foil) of the rolled electrode, measure 200 g of alcohol and pour it into a beaker, cut the electrode into small pieces of 3 cm x 3 cm and place them in the beaker, use a glass rod to slowly stir until the electrode slurry is completely dissolved, pass the solution through a 100 mesh sieve to obtain a filtrate, and place the filtrate in an oven for 30 to 60 min to obtain a solid powder, and the baking temperature is 150 ° C;
[0107] (7) Take the solid powder in (6) and use a laser particle size analyzer to measure the particle size distribution. The particle size distribution diagram is as follows: Figure 4 As shown, the test D 50 The value is 20.192μm;
[0108] (8) The proportions of negative electrode materials and other solid materials are m = 95.5% and n = 4.5%, respectively. The particle size distribution of the powders of the coated and rolled pole pieces is obtained by testing the D 50 The values are D1 = 20.424 μm, D2 = 20.192 μm, and the calculation results are:
[0109]
[0110] Example 3
[0111] (1) preparing a ternary lithium battery positive electrode slurry, wherein the solid raw materials are: ternary main material (NCA), conductive agent (Super-P), conductive carbon (KS-6), polyvinylidene fluoride (PVDF), and the solid mass ratio is 96:2.0:0.5:1.5. The solvent is N-methylpyrrolidone (NMP). The amount of solvent NMP added is adjusted, and the slurry solid content is prepared by stirring and dispersing to obtain 76%;
[0112] (2) Double-sided coating is performed using an extrusion slit coating device. The coated electrode is dried in a suspended blast oven. The weight loss ratio of the coated electrode after baking is ≤1000ppm, and the single-sided coating surface density is 13.21±0.13mg / cm 2 , double-sided coating surface density is 26.42±0.26g / cm 2 , the current collector used for coating is aluminum foil, and the thickness of the aluminum foil is 16±1μm;
[0113] (3) The coated electrode is rolled, and the thickness of the electrode after rolling is 89±1μm (including foil);
[0114] (4) Weigh 50 g (including foil) of the coated electrode, measure 200 g of NMP solution and pour it into a beaker, cut the electrode into small pieces of 3 cm x 3 cm and place them in the beaker, use a glass rod to slowly stir until the slurry on the electrode is completely dissolved, pass the solution through a 100 mesh sieve to obtain a filtrate, and place the filtrate in an oven for baking for 30 to 60 min to obtain a solid powder, and the baking temperature is 180 ° C;
[0115] (5) Take the solid powder in (4) and use a laser particle size analyzer to measure the particle size distribution. 50 The value is 11.480 μm;
[0116] (6) Weigh 50 g (including foil) of the rolled electrode, measure 200 g of NMP solution and pour it into a beaker, cut the electrode into small pieces of 3 cm x 3 cm and place them in the beaker, use a glass rod to slowly stir until the electrode slurry is completely dissolved, pass the solution through a 100 mesh sieve to obtain a filtrate, and place the filtrate in an oven for baking for 30 to 60 min to obtain a solid powder, and the baking temperature is 180 ° C;
[0117] (7) Take the solid powder in (6) and use a laser particle size analyzer to measure the particle size distribution. 50 The value is 10.795μm;
[0118] (8) The proportions of the main positive electrode material and other solid materials are m = 96% and n = 4%, respectively. The particle size distribution of the powder material for coating the electrode and rolling the electrode is obtained by testing the particle size distribution of the powder material. 50 The values are D1 = 11.321 μm, D2 = 11.265 μm, and the calculation results are:
[0119]
[0120] Example 4
[0121] (1) The slurry was prepared according to the slurry ratio in Example 1 and then coated. The coated electrode was dissolved and the particle size distribution was measured using a laser particle size analyzer. 50 The value is 11.321 μm;
[0122] (2) The coated electrode pieces are rolled according to the thickness gradient of 100 μm, 101 μm, 102 μm, 103 μm, 104 μm, 105 μm and 106 μm respectively, and the particle size distribution of the corresponding electrode pieces is tested after treatment. The porosity is calculated according to the formula of this application and recorded as
[0123] (3) Take the electrode pieces with different thicknesses after gradient rolling in (2) and perform SEM test. Import the SEM images into Photoshop software, trim the images to remove the edges, and calculate the porosity to be recorded as
[0124] (4) Comparing the porosities calculated by the two different methods (as shown in Table 1), the relative errors of the porosities calculated by the two methods are within 1%, and it can be considered that the calculation method of the present application has a small error.
[0125] Comparative Example 1
[0126] The difference between Comparative Example 1 and Example 1 is that the porosity of the tested rolled pole pieces is different:
[0127] (1) The pole piece of step (3) of Example 1 was used as the rolled pole piece, and a scanning electron microscopy (SEM) test was performed. The test loading voltage was 10 KV, and a SEM image (such as Figure 5As shown in the figure, the image is imported into Photoshop PS software, the image is trimmed to remove the edges, the overall pixel value of the image is displayed using Photoshop PS software (denoted as A), the solid phase in the image is colored, and the pixels of the colored part are displayed in Photoshop PS software (denoted as B). The porosity of the electrode is:
[0128]
[0129] (2) According to the method of step (1), the overall pixel of the processed image displayed by Photoshop PS software is 1149245 PPI. The solid phase in the image is colored, and the pixel of the colored part displayed by Photoshop PS software is 915374 PPI. The porosity of the electrode is calculated as
[0130] Comparative Example 2
[0131] The difference between Comparative Example 2 and Example 2 is that the porosity of the tested rolled pole pieces is different:
[0132] (1) Take the rolled electrode of step (3) of Example 2 and perform a scanning electron microscope test (SEM) at a test voltage of 10 KV to obtain a SEM image (such as Figure 6 As shown in the figure, the image is imported into Photoshop PS software, the image is trimmed to remove the edges, the overall pixel value of the image is displayed using Photoshop PS software (denoted as A), the solid phase in the image is colored, and the pixels of the colored part are displayed in Photoshop PS software (denoted as B). The porosity of the electrode is:
[0133] (2) According to the method of step (1), the overall pixel of the processed image displayed by Photoshop PS software is 984751 PPI. The solid phase in the image is colored, and the pixel of the colored part displayed by Photoshop PS software is 772838 PPI. The porosity of the electrode is calculated as
[0134] Comparative Example 3
[0135] The difference between Comparative Example 3 and Example 3 is that the porosity of the tested rolled pole pieces is different:
[0136] (1) Take the rolled electrode sheet of step (3) of Example 3 and perform a scanning electron microscope test (SEM) at a test loading voltage of 10 KV to obtain a SEM image (such as Figure 7 As shown in the figure, the image is imported into Photoshop PS software, the image is trimmed to remove the edges, the overall pixel value of the image is displayed using Photoshop PS software (denoted as A), the solid phase in the image is colored, and the pixels of the colored part are displayed in Photoshop PS software (denoted as B). The porosity of the electrode is:
[0137] (2) According to the method of step (1), the overall pixel of the processed image displayed by Photoshop PS software is 1450112 PPI. The solid phase in the image is colored, and the pixel of the colored part displayed by Photoshop PS software is 1125577 PPI. The porosity of the electrode is calculated as
[0138] Comparative Example 4
[0139] The difference between Comparative Example 4 and Example 1 is that the porosity of the tested rolled pole pieces is different:
[0140] Evaluation method of battery pole piece porosity, the specific measurement steps are as follows:
[0141] (1) A graphite negative electrode sheet after chemical formation with a compaction density of 1.6 g / mL was placed in dimethyl carbonate (DMC) for a first immersion treatment for 20 min, dried at 100° C. for 6 h, and then placed in a 40 g / L polyvinylidene fluoride (PVDF) N-methylpyrrolidone (NMP) solution for a second immersion treatment for 20 min, and dried at 100° C. for 6 h; the negative electrode sheet was cut along the thickness direction using argon ion polishing technology to obtain a sheet cross section containing a negative electrode active material layer; the cross section of the negative electrode sheet was scanned and imaged using a backscattering mode of a scanning electron microscope with a magnification of 1000 times and an acceleration voltage of 5 kV to obtain a cross-sectional view of the sheet;
[0142] (2) performing contrast statistics on the image to obtain a curve showing the percentage of pixel points in the image changing with RGB;
[0143] The calculation formula of the porosity N of the graphite negative electrode sheet is:
[0144]
[0145] Wherein, P2 represents the percentage of the number of pixels in the image corresponding to the negative electrode plate, RGBs2 is the RGB value corresponding to the boundary of the pore area of the negative electrode plate, which is 142, wherein the method for determining RGBs2 is: based on the curve of the percentage of the number of pixels P2 in the image corresponding to the negative electrode plate changing with the contrast value RGB, and when (P2) / d(RGB)>k2 and RGB>50, the corresponding minimum value of RGB, wherein d(P1) / d(RGB) is the rate of change of P1 with RGB, k2=0.0001, c is the concentration of the PVDF solution, which is 40 g / L, ρ is the true density of PVDF, 1.78 g / mL, and thus, the calculated porosity of the graphite negative electrode plate is 26.2%.
[0146] Table 1 Comparison of calculation results of two methods in Example 4
[0147]
[0148] By comparing the calculation results of Example 1 and Comparative Example 1: the difference between the two is 20.49%-20.35%=0.14%, and the relative error is (20.49%-20.35%) / 20.35%=0.69%; the calculation method of the present application has a small error, indicating that the electrode porosity can be accurately evaluated.
[0149] By comparing the calculation results of Example 2 and Comparative Example 2: the difference between the two is 21.70%-21.52%=0.18%, and the relative error is (21.70%-21.52%) / 21.70%=0.84%. The calculation method of the present application has a small error, indicating that the electrode porosity can be accurately evaluated.
[0150] By comparing the calculation results of Example 3 and Comparative Example 3: the difference between the two is 22.53%-22.38%=0.15%, and the relative error is (22.53%-22.38%) / 22.38%=0.67%. The calculation method of the present application has a small error, indicating that the electrode porosity can be accurately evaluated.
[0151] In Example 4, two different methods are used to detect the porosity of pole pieces with different rolling thicknesses. The error of the two detection results does not exceed 1%. The error of the method of the present application is relatively small, indicating that the porosity of the pole piece can be accurately evaluated.
[0152] The above detection method of comparative example 4 is a prior art. This method is relatively cumbersome. It mainly images the cross section of the cut pole piece and uses pixel and other data for calculation. The formula calculation is cumbersome and there are many influencing factors, which is not conducive to promotion and use. The equipment used in this method is argon ion polishing technology equipment and scanning electron microscope. The equipment cost is very high (the two imported equipments are close to 10 million), the investment is large, and the equipment maintenance cost is high; the method uses argon ion polishing technology for sample preparation with extremely low efficiency. Generally, it takes 4 to 6 hours to cut a sample, and the cutting size is small. The test results are greatly affected by the sampling position; this technology is only suitable for scientific research and is not easy to promote to industrial production.
[0153] The detection method of Examples 1 to 4 of the present application only needs to measure the median particle size of the particles in the solid slurry of the coated pole piece and the rolled pole piece, and the porosity of the pole piece after the final rolling can be obtained by calculation. The operation is convenient, simple and low-cost.
[0154] The main innovative idea of this application is to estimate the porosity through two different particle sizes and space proportions and the theoretical knowledge that the maximum space proportion of a spherical body is 74.05%. The estimation method is reasonable, easy to operate, and the test results are accurate, which can meet the actual use requirements.
[0155] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0156] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for detecting the porosity of a battery electrode, characterized in that: The detection method comprises the following steps: Step 1: Obtain a solid powder I of the coating material applied to the electrode, and obtain a median particle size D of the solid powder I. 50 The value is recorded as D1; Step 2: Obtain solid powder II of the coating material on the rolled pole piece, and obtain the median particle size D of the solid powder II 50 The value is recorded as D2; Step 3: The porosity of the rolled pole piece is Wherein, m+n=1; m is the weight ratio of the active material in the solid powder I in the solid powder I; n is the weight ratio of the total weight of other components in the solid powder I except the active material in the solid powder I in the solid powder I.
2. The method for detecting the porosity of a battery electrode according to claim 1, characterized in that: The D1 value and / or the D2 value are obtained by testing with a laser particle size analyzer.
3. The method for detecting the porosity of a battery electrode according to claim 2, characterized in that: The model of the laser particle size analyzer is Mastersizer 3000.
4. The method for detecting the porosity of a battery electrode according to any one of claims 1 to 3, characterized in that: The process of obtaining the solid powder I of the coating material on the coated electrode comprises: dissolving the coated electrode in a solvent I to obtain a solution I, and drying the solution I to obtain the solid powder I; And / or, the process of obtaining the solid powder II of the coating material on the rolled pole piece includes: dissolving the rolled pole piece in a solvent II to obtain a solution II, and drying the solution II to obtain the solid powder II.
5. The method for detecting the porosity of a battery electrode according to claim 4, characterized in that: The weight ratio of the coated electrode to the solvent I is 1:(2-5); and / or, after the coated electrode is dissolved in the solvent I, the filtrate after filtering through a 100-mesh sieve is the solution I; and / or, the weight ratio of the rolled pole piece to the solvent II is 1:(2-5); And / or, after the rolled pole piece is dissolved in the solvent II, the filtrate obtained after filtering through a 100-mesh sieve is the solution II.
6. The method for detecting the porosity of a battery electrode according to claim 4 or 5, characterized in that: The temperature of the drying process I is 150-200° C., and the time of the drying process I is 30-60 min. And / or, the temperature of the drying II is 150-200° C., and the time of the drying II is 30-60 min; And / or, the drying I or the drying II is carried out by drying in a suspended air-blast oven.
7. The method for detecting the porosity of a battery electrode according to any one of claims 4 to 6, characterized in that: The battery pole piece is a positive pole piece or a negative pole piece of a ternary lithium battery; and / or, the solvent used to dissolve the positive electrode plate is selected from one or more of N-methylpyrrolidone, dimethylformamide and ethylene glycol; And / or, the solvent used to dissolve the negative electrode plate is selected from one or more of pure water, acetone, methanol, ethanol and isopropanol.
8. The method for detecting the porosity of a battery electrode according to any one of claims 1 to 7, characterized in that: The active material is a positive electrode active material or a negative electrode active material; And / or, the other components except the active material include a conductive agent, a binder and an auxiliary agent.
9. The method for detecting the porosity of a battery electrode according to claim 8, characterized in that: The positive electrode active material includes one or more of lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and lithium cobalt oxide; And / or, the negative electrode active material includes one or more of graphite, silicon carbon and silicon oxygen.
10. The method for detecting the porosity of a battery electrode according to claim 8 or 9, characterized in that: The conductive agent includes one or more of conductive graphite, conductive carbon black, carbon nanotubes and carbon fibers; And / or, the binder includes one or more of polyvinylidene fluoride, polymethyl methacrylate, polytetrafluoroethylene, styrene-butadiene rubber and sodium carboxymethyl cellulose; And / or, the auxiliary agent includes one or more of lithium carbonate, oxalic acid, vinyl sulfate, dimethyl sulfate and diethyl oxalate.
Citation Information
Patent Citations
Electrode plate porosity measurement and calculation method
CN106684330A
Porosity determination method of lithium ion battery pole piece
CN112362549A
Method and system for testing liquid absorption porosity of pole piece
CN116087064A
Indication paste for checking porosity of anodic coating on copper
SU1383159A1
Electrochemical device and electronic device
US20220328832A1
Cited By
Preparation method of secondary battery, secondary battery, energy storage system and electric equipment
CN120356904A
Porosity measurement method and system
WO2026175022A1